Analysis of the Use of Constructive Journalism in the News 'Police Shoot Police' in the Online Media Tirto.id: Analisis Penggunaan Jurnalisme Konstruktif dalam Berita 'Polisi Tembak Polisi' di Media Online Tirto.id - Qorib, Fathul; Kristie, Erasa; Hakim, Lukman (Universitas Muhammadiyah Sidoarjo, 2024)
The coverage of the